Pengaruh Thin Capitalization, Risiko Perusahaan, dan Kepemilikan Asing terhadap Penghindaran Pajak - Nulhakim, Salwan; Tarmidi, Deden (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine the effect of thin capitalisasion, company risk, and foreign ownership on tax avoidance. Consumer goods manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023 were the units of analysis in this study. There were 44 companies selected through purposive sampling, and after removing outliers, there were 123 firm-year data analysed. The analysis technique used was multiple linear regression analysis. The results showed that thin capitalisation had a positive effect on tax avoidance, while corporate risk had a negative effect on tax avoidance, and foreign ownership had no effect on tax avoidance.